Variance component and heritability estimates of early growth traits in the Elsenburg Dormer sheep stud - Wyk, J.B. van; Erasmus, G.J.; Konstantinov, K.V. (1993)
Total of 8909 birth weight and 7740 weaning weight records, from the progeny of 215 sires, collected from 1943 to 1990 from the Elsenburg Dormer sheep stud, were analysed. Additive genetic variance and heritability estimates for birth weight (BW), weaning weight (WW), average daily gain (ADG) and the Kleiber ratio (KL) were obtained by Restricted Maximum Likelihood (REML) procedures fitting three different models. Estimates were severely biased upwards when an animal model, ignoring maternal effects, was fitted. A sire model yielded more realistic estimates of direct additive variance. Estimates of maternal genetic variance and corresponding heritabilities (h2m) were higher than estimates for direct additive variance and heritability (h2a) when fitted simultaneously in an animal model. The genetic correlations between direct and maternal influence were consistently negative but the proportion of cov (a, m) to phenolypic variance decreased from birth to weaning. The heritability estimales were as follows: BW = 0.12, 0.42, 0.16, 0.43; WW = 0.12, 0.34, 0.13, 0.20; ADG = 0.13, 0.31, 0.13, 0.18; KL = 0.13, 0.26, 0.14, 0.14 for a sire model, animal model, animal model direct effects (h2a) and animimal model maternal effects (h2m), respectively.